2017
DOI: 10.1136/bmj.j1334
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and risk of suicide: cohort study of 548 721 adolescents and young adults in Sweden

Abstract: ObjeCtiveTo examine the relation between childhood adversity, the role of school performance, and childhood psychopathology and the risk of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 27 publications
5
84
0
1
Order By: Relevance
“…In particular, future studies should investigate the role of psychosocial factors such as family adversities or peer victimization, which were associated with irritability and suicidal behaviors in previous studies. 30,35,42 Such studies also could suggest possible targets for psychosocial interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, future studies should investigate the role of psychosocial factors such as family adversities or peer victimization, which were associated with irritability and suicidal behaviors in previous studies. 30,35,42 Such studies also could suggest possible targets for psychosocial interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also further investigate the more elusive subjective aspects of suicide risk, such as SI, as well as implicated psychological constructs such as hopelessness, rumination, and anhedonia [209][210][211], which may be relevant across diagnoses. Similarly, social experiences such as childhood maltreatment and peer bullying form a strong prelude to STB in later life [208,212,213], and impact on the neural structures implicated in STB (e.g., DMPFC structure and function [214,215]). Therefore, adverse experiences should be taken into account in future studies on the neurobiology of STB.…”
Section: Future Directionsmentioning
confidence: 99%
“…Besides mental disorders, some of the other well‐documented risk factors emerged in the present study only on the univariate level, such as adverse childhood experiences (both suicide and sudden violent death), being sexually assaulted (suicides), and severity of stressful life events in the previous year (both groups). Previous research indicated that independently of other psychosocial and psychiatric factors, early and late life adversities, and particularly accumulated adversities, are a risk factor for suicidal behavior (Björkenstam, Kosidou, & Björkenstam, ; Fergusson et al, ; Foster, ; Joiner et al, ; Liu & Miller, ; Read, Agar, Barker‐Collo, Davies, & Moskowitz, ; Séguin, Renaud, Lesage, Robert, & Turecki, ). However, a new finding is the importance of adverse life events as a risk factor for sudden violent death.…”
Section: Discussionmentioning
confidence: 99%